Synaptic Vesicle Glycoprotein 2A: Features and Functions - Rossi, Rachele; Arjmand, Shokouh; Bærentzen, Simone Larsen; Gjedde, Albert; Landau, Anne M. (Frontiers in Neuroscience, 2022)
In recent years, the field of neuroimaging dramatically moved forward by means of the expeditious development of specific radioligands of novel targets. Among these targets, the synaptic vesicle glycoprotein 2A (SV2A) is a transmembrane protein of synaptic vesicles, present in all synaptic terminals, irrespective of neurotransmitter content. It is involved in key functions of neurons, focused on the regulation of neurotransmitter release. The ubiquitous expression in grey matter regions of the brain is the basis of its candidacy as a marker of synaptic density. Following the development of molecules derived from the structure of the anti-epileptic drug levetiracetam, which selectively binds to SV2A, several radiolabeled markers have been synthetized to allow the study of SV2A distribution with positron emission tomography (PET). These radioligands permit the evaluation of in vivo changes of SV2A distribution held to be a potential measure of synaptic density in physiological and pathological conditions. The use of SV2A as a biomarker of synaptic density raises important questions. Despite numerous studies over the last decades, the biological function and the expressional properties of SV2A remain poorly understood. Some functions of SV2A were claimed, but have not been fully elucidated. While the expression of SV2A is ubiquitous, stronger associations between SV2A and ϒ amino butyric acid (GABA)-ergic rather than glutamatergic synapses were observed in some brain structures. A further issue is the unclear interaction between SV2A and its tracers, which reflects a need to clarify what really is detected with neuroimaging tools. Here, we summarize the current knowledge of the SV2A protein and we discuss uncertain aspects of SV2A biology and physiology. As SV2A expression is ubiquitous, but likely more strongly related to a certain type of neurotransmission in particular circumstances, a more extensive knowledge of the protein would greatly facilitate the analysis and interpretation of neuroimaging results by allowing the evaluation not only of an increase or decrease of the protein level, but also of the type of neurotransmission involved.